High‐performance user plane function (UPF) for the next generation core networks. Issue 6 (3rd November 2020) - Chen, Whai‐En; Liu, Chia Hung
Abstract : Comparing with previous mobile communications, the fifth generation (5G) mobile communication provides three different types of services including enhanced mobile broadband, massive machine type communications, and ultra‐reliable and low latency communications. To fulfil various requirements of these services, 5G defines new technologies and architectures such as the next‐generation core network (NGC) and the new radio of the access network (5G‐AN). The user plane function (UPF), which is an essential component in 5G NGC, connects 5G‐AN and packet data networks (e.g. internet). Typically, the UPF provides the tunnelling, internet protocol/port translation, and forwarding functions. To provide flexibility and scalability deployment for 5G NGC, this study virtualises the UPF by using the Docker container. However, the virtualisation architecture degrades the performance of the UPF, and the performance of the UPF dominates the performance (e.g. throughput) of the 5G user‐plane transmission. To provide high‐performance packet processing, this study utilises Intel Data Plane Development Kit to develop the UPF, reduces the number of memory copy on header processing, and investigates the CPU core allocation methods for the UPF deployment. Based on the results of this study, the proposed UPF can provide the UPF functions and process the packets up to 40 Gbps on a x86‐based platform.